Birthweight and cardiometabolic risk patterns in multiracial children - Sun, D.; T. Wang; Heianza, Y.; Huang, T.; Shang, X.; Lv, J.; S Li; Harville, E.; Chen, W.; Fonseca, V.; Qi, L. (Int J Obes (Lond)Int J Obes (Lond), 2018)
BACKGROUND/OBJECTIVES: Prenatal growth, which is widely marked by birthweight, may have a pivotal role in affecting the lifelong risk of cardiometabolic disorders; however, comprehensive evaluation of its relations with childhood cardiometabolic risk patterns and the ethnic and gender disparities in national representative populations is still lacking. The aim of this study was to evaluate the associations between birthweight and comprehensive patterns of cardiometabolic risk in a nationally representative sample of children and adolescents. SUBJECTS/METHODS: Prospective analyses were performed using data from 28 153 children 0 to 15 years in the National Health and Nutrition Examination Survey from 1999 through 2014. We defined childhood cardiometabolic disorders using standard definitions for obesity, high blood pressure, hyperglycemia and dyslipidemia. RESULTS: Five birthweight categories <2.5, 2.5-3.0, 3.0-3.5, 3.5-4.2 and 4.2 kg accounted for 8.2%, 17.9%, 35.7%, 27.9% and 10.4% of the population, respectively. In all children, with increasing birthweight, we observed significantly increasing trends of the risk of general and central obesity (P for trend <0.01) and significantly decreasing trends of the risk of high systolic blood pressure (SBP), high HbA1c and low high-density lipoprotein cholesterol (HDL-C) (P for trend <0.05). The associations were independent of current body mass index (BMI). In addition, we found that the relations of birthweight with high waist circumference in Black children showed U-shape, as well as high SBP in Mexican and Hispanic children. Moreover, we found that the associations of low birthweight with high SBP and low HDL-C appeared to more prominent significant in boys, whereas the inverse association with high HbA1c was more evident in girls. CONCLUSIONS: Our data indicate that birthweight is significantly related to childhood cardiometabolic risk, independent of current BMI, and the associations exhibit race and gender-specific patterns.